The influence of the ethic culture and intellectual capital on local government performance: Evidence from Indonesia - Prasetya, Buntoro Heri; Sudibyo, Yvone Agustine; Gunawan, Juniati; Khomsiyah, Khomsiyah (Technium Social Sciences Journal, 2021)
The provision of public services by local governments in Indonesia is considered unsatisfactory. By theoretically ethical culture and intellectual capital play an important role on organization performance. This study aims to analyze the effect of ethical culture, and intellectual capital on Indonesian local government performance. The research sample was 53 districts / cities in Indonesia which were selected using cluster sampling method. This study uses ethical regulations and reporting on allegations of unethical behavior as a proxy for ethical culture, while intellectual capital and performance of local governments are measured by indicators used in assessing the performance of local government administration. The study results conclude that ethical culture and intellectuals have a positive effect on local government performance. That conclusion has an impact on the importance for local governments to induce and disseminate ethical culture and manage intellectual capital effectively. The results of this study also support the mindset of bureaucratic reform that is currently running in Indonesia